Pulmonary vascular dysfunction in ARDS - Ryan, Donal (Ann Intensive Care, 2014)
Acute respiratory distress syndrome (ARDS) is characterised by diffuse alveolar damage and is frequently complicated by pulmonary hypertension (PH). Multiple factors may contribute to the development of PH in this setting. In this review, we report the results of a systematic search of the available peer-reviewed literature for papers that measured indices of pulmonary haemodynamics in patients with ARDS and reported on mortality in the period 1977 to 2010. There were marked differences between studies, with some reporting strong associations between elevated pulmonary arterial pressure or elevated pulmonary vascular resistance and mortality, whereas others found no such association. In order to discuss the potential reasons for these discrepancies, we review the physiological concepts underlying the measurement of pulmonary haemodynamics and highlight key differences between the concepts of resistance in the pulmonary and systemic circulations. We consider the factors that influence pulmonary arterial pressure, both in normal lungs and in the presence of ARDS, including the important effects of mechanical ventilation. Pulmonary arterial pressure, pulmonary vascular resistance and transpulmonary gradient (TPG) depend not alone on the intrinsic properties of the pulmonary vascular bed but are also strongly influenced by cardiac output, airway pressures and lung volumes. The great variability in management strategies within and between studies means that no unified analysis of these papers was possible. Uniquely, Bull et al. (Am J Respir Crit Care Med 182:1123–1128, 2010) have recently reported that elevated pulmonary vascular resistance (PVR) and TPG were independently associated with increased mortality in ARDS, in a large trial with protocol-defined management strategies and using lung-protective ventilation. We then considered the existing literature to determine whether the relationship between PVR/TPG and outcome might be causal. Although we could identify potential mechanisms for such a link, the existing evidence does not allow firm conclusions to be drawn. Nonetheless, abnormally elevated PVR/TPG may provide a useful index of disease severity and progression. Further studies are required to understand the role and importance of pulmonary vascular dysfunction in ARDS in the era of lung-protective ventilation.